2021
DOI: 10.3390/cancers13051118
|View full text |Cite
|
Sign up to set email alerts
|

Fighting Drug Resistance through the Targeting of Drug-Tolerant Persister Cells

Abstract: Designing specific therapies for drug-resistant cancers is arguably the ultimate challenge in cancer therapy. While much emphasis has been put on the study of genetic alterations that give rise to drug resistance, much less is known about the non-genetic adaptation mechanisms that operate during the early stages of drug resistance development. Drug-tolerant persister cells have been suggested to be key players in this process. These cells are thought to have undergone non-genetic adaptations that enable surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 101 publications
3
56
0
Order By: Relevance
“…For many decades, studies have pointed genetic mutations as the central mechanism of resistance acquisition to targeted therapy [20]. However, growing evidence challenges this consensus, indicating that non-genetic heterogeneity and cell plasticity actively participate in drug tolerance [21][22][23]. Recently, new profiling techniques, like FATE-seq, have been carried out to dissect the non-genetic mechanisms of resistance [24].…”
Section: Discussionmentioning
confidence: 99%
“…For many decades, studies have pointed genetic mutations as the central mechanism of resistance acquisition to targeted therapy [20]. However, growing evidence challenges this consensus, indicating that non-genetic heterogeneity and cell plasticity actively participate in drug tolerance [21][22][23]. Recently, new profiling techniques, like FATE-seq, have been carried out to dissect the non-genetic mechanisms of resistance [24].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of DTPs in the bone marrow of cancer patients after therapeutic intervention, a condition termed the minimal residual disease, indicates a high probability of cancer relapse. It has been previously hypothesized that DTP cells originate from the tumour cells residing in hybrid or mesenchymal states along the EMT/MET spectrum [ 125 , 126 ].…”
Section: Axl Epithelial-mesenchymal Plasticity Drug Tolerant Persister Cells and Cancer Metastasismentioning
confidence: 99%
“…Although tolerant cells may pre-exist in the tumor, it has been shown that some cells become DTPs through EMT and phenotype plasticity following drug exposure [ 101 , 102 , 103 ].While there is currently no consensus on specific markers associated with DTPs [ 103 ], the accumulation of DTPs can occur in different tumor types by seemingly different mechanisms.…”
Section: Drug-tolerant Persisters and Post-treatment Lineage Heterogeneitymentioning
confidence: 99%
“…Once drug exposure was stopped, DTPs resumed growth and reacquired EGFR TKI sensitivity, suggesting a nonmutational mechanism of resistance [ 105 ]. DTPs can survive for months, allowing time for the development of new resistant clones through the acquisition of driver mutations and creating a link between nonmutational and mutational resistance mechanisms [ 103 , 106 ]. Therefore, an increased understanding of cellular plasticity and of the mechanisms surrounding the development DTPs will be key in preventing cancer drug tolerance.…”
Section: Drug-tolerant Persisters and Post-treatment Lineage Heterogeneitymentioning
confidence: 99%